BACKSTOP SECURITY SYSTEM USING ARDUINO UNO WITH ESP8266MOD - G, Arun Francis (International Journal of Psychosocial Rehabilitation, 2020)
Web of Things or IoT to put it plainly, is making gadgets and items more brilliant by connecting them to the web. IoT has promising applications for smart home, wearable devices and more. The primary objective of this project is to stop the intruder even if the smart security system is broken and it reduces the man power by designing and implementing a security system named as Backstop Security System (BSS) [1] that offers tractable through a Babysat mobile phone and PC by betokens of IoT. Our project proposes security system using IoT environment which intimates’ intrusion in Home, Bank, Airports, Offices, University or any location and typically report to the administrator. The influence acquired by leaning toward this framework over comparative sort of existing frameworks is that the cautions send through Android application to make an intrusion alert over the Arduino UNO and Node MCU managed system can be received by user at any distance and to the nearby security personal’s. Not only that, it also makes the intruder to loss his consciousness by electrocuting them with the help of the stun gun which is embedded inside the handle of the respective door.